La psicomotricidad y su importancia en el desarrollo de las habilidades de comprensión lectora de los niños y niñas de 5 a 6 años de primer año de educación básica de la escuela Manuel Matheu en la provincia de Cotopaxi cantón Latacunga parroquia Pastocalle en el año lectivo 2014-2015 - Guachi Chiluiza, Lourdes Marlene (2015)
The research was aimed at the study of motor skills and their influence on reading comprehension, theme relevance in today's world as infants develop body movements that are an essential part of being human is why we need a full guide and safe to shape and promote their skills and psychomotor skills so as he emphasized that the first teachers to be enriching and give initiative in motor prontitud are parents responsible for the guidance and teaching - learning while remaining in their homes supplementing infant education is teaching school must exploit their potential based on recreational, drama, children's stories and other methodological strategies that reference to develop excellent traction and thus benefit the animation of a reading comprehension, attitude that teachers must possess to stimulate psychomotor skills necessary for the process of good reading comprehension. That is why the influence of psychomotor in the infant resulted in the overall development of their skills and abilities to be more autonomous entity in their daily activities effectively. Under all this showed that the infant's motor skills is essential for the progress of young children is flexible and evolve every day to strengthen its overall development action.